(3JGL GdYQhS aj TQM GdbGehSs - (3eMeO Hf eMeO Hf eMeO Hf YHO GdQGRb, GdSjO eQJVj GdMSjfj GdRHjOj,CHh GdajV , J (B1205 (3g` s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s ((3YWaI GdYSGd HeUQ s)
(3ChdgG (B:s
(3ef Chd HGH MQa GdUGO GdegedI , bhdg (B: (3HGH GdUGO (B: (3hgh MQa ef GdMQha GdYTQI GdegehSI , hGdRGi hGdSjf hGdUGO ai MjR hGMO hdG JCJda GdUGO eY GdSjf s
(3BNQgG (B:s
(3Edi BNQ HGH GdWGA GdegedI , bhdg (B: (3bGd GdCYTi(B: (3dbO efhG HJjLGf SGW KHJ GPG bjd dg jYGW hbGd GdLeMi (B: (3jYGW (B: (3GSJZGKI hRLQ s
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs